Role of low fluence Q-Switched laser in the treatment of hyper pigmented skin disorders - Irfan Ahmed Shaikh (Journal of Pakistan Association of Dermatologists, 2022)
Objective To determine the efficacy and safety of Q-Switched Nd-YAG laser in the treatment of various pigmentary cutaneous disorders. Methods This study was carried out at Department of Dermatology Shaheed Mohtarma Benazir Bhutto Skin Complex Larkana from May 2017 to November 2017. A total of 40 patients, who fulfilled the inclusion criteria (who failed the conventional treatment) were enrolled for this study after taking informed consent. The diagnosis of all cases was made on clinical basis. Spot sizes vary from 3cm to 20cm were treated with Q-switched laser on weekly basis. The result of pigmentation was assessed initially after 3 sessions followed by every week session with grading and photographs. Adverse effects were recorded after each visit. Results A total of 40 cases participated, 27 (67.5%) out of 40 were of melasma, 11 (27.5%) were of Nevus of ota and 2 (5%) were of Tattoo Marks. Out of 27 (67.5%) cases of melasma 5 (18.5%) showed minimum hyper pigmentation as before treatment with Nd YAG Laser were graded as severe hyper pigmentation, 7 (27.9%) showed moderate hyper pigmentation and 15 (55.5%) cases didn’t gave any response and discontinued the treatment. Out of 11 (27.5%) cases of Nevus of ota 8 (27.7%) showed marked improvement and 3 (27.2%) showed moderate improvement. The 2 cases of Tattoo Marks gave good response and were males. The treatment response was statistically significant (p=0.92) and was statistically no significant gender difference (p=.819). Conclusion we conclude that Q-Switched Nd YAG laser is good modality to treat various pigmentory skin disorders in which conventional treatment is less satisfactory.